Risk Disclosure in UK Companies Annual Reports - Yampolskaya, Natalya (2006)
This dissertation discusses the UK companies practices in disclosing risk-related information in their corporate annual reports. In particular, the paper attempts to see whether the volume of risk and risk management disclosures provided by companies in their annual reports have changed during the period from the year 2001 until the year 2005. The paper is also seeking to demonstrate if there is a correlation between the volume of risk disclosures provided by companies and the size of those companies. In addition, the research describes some interesting aspects of risk disclosure in companies annual reports depending on risk category.